UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI PINANG (Areca catechu L.) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli, Shigella dysentriae, DAN Salmonella typhi - Sitompul, Erly; Hafizullah, Ahmad; Silalahi, Yosy Cinthya Eriwaty; Telaumbanua, Realisni (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
One of the medicinal plants is the areca nut (Areca catechu L.) from the Arecae family which has the potential as an anticancer having antioxidant and antimutagenic, astringent, and anthelmintic effects. Areca nut seeds contain alkaloids, such as arekoline, arekolidine, arekain, guvakolin, guvasine and isoguvasine. This study aims to determine the characteristics of the betel nut (Areca catechu L.) simplicia, class of compounds, and the antibacterial activity of the ethanol extract of areca nut (Areca catechu L.) against the growth of Escherichia coli, Shigella dysentriae, and Salmonella typhi bacteria. The method used is the ethanol extract of areca nut (Areca catechu L.) obtained from the maceration process with 96% ethanol. The results of phytochemical screening showed that the ethanolic extract of areca nut (Areca catechu L.) contains a group of alkaloid compounds, tannins, flavonoids, saponins, and triterpenoids. The effect of giving young betel nut ethanol extract to Escherichia coli, Shigella dysentriae, and Salmonella typhi bacteria was indicated by the formation of an inhibition zone of optimum concentration. The ethanol extract of old betel nut against Escherichia coli, Shigella dysentriae, and Salmonella typhi bacteria was characterized by the formation of an optimum concentration inhibition zone. Based on the results, it can be concluded that the ethanol extract of areca nut (Areca catechu L.) has antibacterial activity against Escherichia coli, Shigella dysentriae, and Salmonella typhi.